2019
DOI: 10.1186/s12575-019-0110-4
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating osa-MIR156f Expression by D18 Promoter to Regulate Plant Architecture and Yield Traits both in Seasonal and Ratooning Rice

Abstract: BackgroundRice (Oryza sativa L.) feeds more than half of the world’s population. Ratooning rice is an economical alternative to the second seasonal rice, thus increasing the yield of ratooning rice is highly important.ResultsHere we report an applicable transgenic line constructed through the manipulation of osa-MIR156f expression in rice shoot using the OsGA3ox2 (D18) promoter. In seasonal rice, the D18–11 transgenic line showed moderate height and more effective tillers with normal panicle. In ratooning rice… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
1
7
0
Order By: Relevance
“…Combining the facts that both the OsMTD1 RNA i lines and mutant lines with a T-DNA insertion into the region of this CNV in two-copy ZH11 displayed multitillering phenotypes ( Liu et al, 2015 ), it is clear that OsMTD1 alone could be regarded as an executive factor for tillering and leaf angle. For the second gene in OsMTD1 -located CNV, i.e., pri-miR156f , we had demonstrated that the osa-miR156f plays crucial roles in rice tiller development ( Liu et al, 2019 ), which is consistent with previous reports that high-level miR156 causes a bushy phenotype ( Schwab et al, 2005 ; Xie et al, 2006 ). The effects of OsmiR156f on leaf angle are also verified ( Supplementary Figure 5 ; Miao et al, 2019 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Combining the facts that both the OsMTD1 RNA i lines and mutant lines with a T-DNA insertion into the region of this CNV in two-copy ZH11 displayed multitillering phenotypes ( Liu et al, 2015 ), it is clear that OsMTD1 alone could be regarded as an executive factor for tillering and leaf angle. For the second gene in OsMTD1 -located CNV, i.e., pri-miR156f , we had demonstrated that the osa-miR156f plays crucial roles in rice tiller development ( Liu et al, 2019 ), which is consistent with previous reports that high-level miR156 causes a bushy phenotype ( Schwab et al, 2005 ; Xie et al, 2006 ). The effects of OsmiR156f on leaf angle are also verified ( Supplementary Figure 5 ; Miao et al, 2019 ).…”
Section: Discussionsupporting
confidence: 90%
“…The comparative analysis indicated the sequences of OsMTD1 are identical in all cultivars, and pre-miR156f has identical sequences in all indica cultivars (Zhenshan 97, Minghui 63, 93–11, Shuhui 498, and RP Bio-226) but shows sequence differences in japonica cultivars (Nipponbare and ZH11); however, the final functional sequences of osa-miR156f and osa-miR156f ∗ are completely identical in all investigated cultivars ( Supplementary Figure 1 ). It is noteworthy that the osa-miR156 was confirmed to be positively correlated with rice tillering ( Supplementary Figure 2 ; Schwab et al, 2005 ; Xie et al, 2006 ; Wang L. et al, 2015 ; Liu et al, 2019 ), whereas the tiller number comparison in cultivars with different CNV copies showed that the OsMTD1 -located CNV region negatively affects rice tillering ( Figures 2B,D ). The osa-miR156f is aggressively antagonistic to OsMTD1 -located CNV effect on tillering ability, suggesting that OsMTD1 plays a vital role in the CNV.…”
Section: Resultsmentioning
confidence: 95%
“…In this case also, MAS was implemented to concomitantly upgrade the appearance and enhance the grain yield (Wang et al, 2012). Additionally, OsmiR156 was reported to regulate the tillering-associated genes (TB1, LAX1, and DWARF 53) (Liu Q. et al, 2019). These studies demonstrated that miR156 is a crucial regulator in rice.…”
Section: Genomics and Transcriptomics In Rice Trait Improvementmentioning
confidence: 95%
“…Whether these or other signals are involved in differentially regulating the temporal expression of miR156 to orchestrate delayed phase transitions in annuals versus perennials is unknown. Nonetheless, direct manipulation of miR156 levels under the gibberellin 3 oxidase 2 (GA3ox2) promoter increased branching and overall grain yield in both seasonal and ratooning rice, suggesting a strong link between developmental age, architecture, and productivity ( Liu et al., 2019 ).…”
Section: Introductionmentioning
confidence: 99%